2009
DOI: 10.1111/j.1537-2995.2009.02334.x
|View full text |Cite
|
Sign up to set email alerts
|

BLOOD COMPONENTS: A novel approach to pathogen reduction in platelet concentrates using short‐wave ultraviolet light

Abstract: UVC irradiation is a potential new method for pathogen reduction in PCs. The data obtained until now justify further development of this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
189
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(211 citation statements)
references
References 60 publications
20
189
0
2
Order By: Relevance
“…Während der Entwicklung des UVCVerfahrens wurde die Inaktivierung von Viren, Bakterien und Protozoen in Abhängigkeit von der UVC-Dosis untersucht. Dabei zeigte sich mit steigender UVC-Dosis eine Zunahme der Inaktivierungseffizienz [123]. Das THERAFLEX Verfahren ist gegenwärtig für TK in Additivlösung mit einer UV-Dosis von 0,2 J/cm² ausgelegt [121].…”
Section: Unerwünschte Effekte Der Pathogeninaktivierung Mit Mirasol®unclassified
See 1 more Smart Citation
“…Während der Entwicklung des UVCVerfahrens wurde die Inaktivierung von Viren, Bakterien und Protozoen in Abhängigkeit von der UVC-Dosis untersucht. Dabei zeigte sich mit steigender UVC-Dosis eine Zunahme der Inaktivierungseffizienz [123]. Das THERAFLEX Verfahren ist gegenwärtig für TK in Additivlösung mit einer UV-Dosis von 0,2 J/cm² ausgelegt [121].…”
Section: Unerwünschte Effekte Der Pathogeninaktivierung Mit Mirasol®unclassified
“…Es wurden nur geringere Änderungen im Proteom der THERAFLEX-behandelten Thrombozyten gefunden. Es sind vor allem Proteine betroffen, die an der Agonisten-induzierten Veränderung der Zellmorphologie (shape change) und der Adhäsion beteiligt sind [123].…”
Section: Unerwünschte Effekte Der Pathogeninaktivierung Mit Theraflexunclassified
“…Physical methods such as heat treatment and Nanofiltration were applied in plasma fractions [19]. Harald et al reported a method using short-wave ultraviolet light (UVC) to reduce pathogen in platelet concentrates by its direct interaction with nucleic acids [20]. Under the illumination of 0.4 J/ cm 2 UVC, no bacterial growth was observed 6 days after treatment.…”
Section: Pi/pr By Psoralensmentioning
confidence: 99%
“…Another inactivation method, which is based on the microbiocidal and virucidal properties of the short-wave ultraviolet light alone is under development. New inactivation method, which is based on the microbiocidal and virucidal properties of the short-wave ultraviolet light alone (200-280 nm) is under development which inactivates pathogens mainly by its direct interaction with nucleic acids [10]. …”
Section: Newer Ideasmentioning
confidence: 99%